Google classroom : An online platform for teaching English - Tommy Hastomo; Febriyantina Istiara; Eva Nurchurifiani (Aksara: Jurnal Bahasa dan Sastra, 2021)
In the development of the internet era, classroom learning changes from traditional teaching to online learning. The purpose of this research is to report action research that was carried out to investigate the effectiveness of google classroom on students’ learning performance in STKIP PGRI Bandar Lampung. The participants were 25 students studying English. The researchers conducted some exercises, discussions, quizzes, and activities on Google Classroom based on three lesson plans that were applied to teach the students in the writing course. Analysis of students’ second writing shows a significant improvement in students’ writing. The students have positive perceptions towards using Google Classroom in language learning based on a post-treatment questionnaire result.